ChemInform Abstract: Efficient and Scalable Synthesis of 4‐Carboxy‐Pennsylvania Green Methyl Ester: A Hydrophobic Building Block for Fluorescent Molecular Probes. Issue 25 (24th June 2014) - Woydziak, Zachary R.; Fu, Liqiang; Peterson, Blake
Abstract The improved reaction conditions allow the synthesis of multigram quantities of the title compound (VIII) in 28% overall yield.